Differential toxigenic behaviour of Alternaria alternata isolates from citrus fruits - GEETA SUMBALI, ROZY BAMBA* and (Indian Phytopathology, 2006)
An investigation was conducted to elucidate differential toxigenic behaviour of pathogenic Alternaria alternata isolates from diseased citrus fruits and from the surface of healthy citrus fruits viz., mandarin orange var. Nagpur Santra, kinnow mandarin and sour lime. Majority of the tested A. alternata isolates produced tenuazonic acid (TeA) as the main mycotoxin whereas, alternariol (AOH) and altertoxin (ATX-I) were not detected from the diseased citrus tissues even by HPLC method. Highest amount of TeA was detected from A. alternata infected mandarins (6.3 to 9.4 mg/kg), followed by infected sour limes (1.6 to 6.1 mg/kg) and kinnow mandarins (0.4 to 1.9 mg/kg). Toxicity of tenuazonic acid is well documented but its tolerance limit in food and feed is not yet fixed.